Saka Guru dan Atap Tumpang Tiga : Keunikan Arsitektur Masjid Agung Demak - Ayu Ifrochah; Ummi Roro Kusuma Dewi; Miftakhul Khairi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The Great Mosque of Demak is one of the most significant Islamic historical heritages on the island of Java. Built in the 15th century by Raden Fatah and Walisongo, this mosque symbolizes the beginning of the glory of Islam in the archipelago. Its distinctive architecture depicts the acculturation of Javanese and Islamic culture, with unique elements such as the three-tiered pyramid roof which symbolizes faith, Islam and ihsan, as well as the